The community property regime in the context of conducting a business activity and acquisition of shares in a limited liability company - Czernicki, Przemysław (Management and Administration Journal, 2019)
The issue, regarded as an important aspect of conducting a business activity, namely the legal effects of acquisition, financed from community property, of shares in a limited liability company by spouses who have chosen the community property regime, has long been debated among representatives of legal science. It also brings about a considerable difficulty in the practice of economic trading, which is an important issue as companies of this type are the most popular form of conducting a business activity in Poland. Doubts concerning the shape of legislative solutions regulating the issue in question are unquestionably exacerbated by the fact that the said regulations belong to both, the sphere of family law and the sphere of commercial companies law, which makes us expect appropriate legislative intervention in this respect. This article aims to present the issue concerning acquisition of shares in limited liability companies on the basis of the Family and Guardianship Code, which is further considered in a subsequent publication that aims to present the solutions adopted in this respect in the Code of Commercial Partnerships and Companies.